2021
DOI: 10.1002/ajh.26207
|View full text |Cite
|
Sign up to set email alerts
|

Low dose venetoclax as a single agent treatment of plasma cell malignancies harboring t(11;14)

Abstract: Approximately 20% of newly diagnosed multiple myeloma (NDMM) patients harbor t (11;14), a marker of inferior prognosis, resulting in up-regulation of CCND1. These patients respond to BCL2 inhibitor experimental drug venetoclax. Furthermore, t(11;14) is reported to be associated with increased BCL2/MCL1 ratio. We investigated the use of venetoclax (400 mg daily) in a cohort of 25 multiple myeloma (MM) and ALamyloidosis patients harboring t(11;14) and assessed safety and efficacy. Efficacy was assessed by respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Subsequently, multiple case reports and case series demonstrated the activity of venetoclax, both in single agent and in combinations, in AL amyloidosis. 8,10,[33][34][35] Our experience with venetoclax-based combination regimens in relapsed/ refractory AL amyloidosis from a multicenter retrospective cohort study showed a haematological response rate of 81% and VGPR or better in 78% of t (11;14) patients. 36 The median PFS was not reached for t(11;14) patients and 6.7 months for non-t(11;14) patients (p < 0.01).…”
Section: Oral Acyclovir or Valacylovir For The Duration Of Therapy Fo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, multiple case reports and case series demonstrated the activity of venetoclax, both in single agent and in combinations, in AL amyloidosis. 8,10,[33][34][35] Our experience with venetoclax-based combination regimens in relapsed/ refractory AL amyloidosis from a multicenter retrospective cohort study showed a haematological response rate of 81% and VGPR or better in 78% of t (11;14) patients. 36 The median PFS was not reached for t(11;14) patients and 6.7 months for non-t(11;14) patients (p < 0.01).…”
Section: Oral Acyclovir or Valacylovir For The Duration Of Therapy Fo...mentioning
confidence: 99%
“…7 Several retrospective cohort studies also demonstrated impressive activity of venetoclax in patients harbouring t (11;14). [8][9][10] However, the initial optimism about venetoclax was tempered by data from BELLINI trial, which showed a higher mortality in the venetoclax arm despite deeper haematological responses, likely due to infection-related deaths in the non-t (11;14) cohort. 11 Currently, venetoclax continues to be used offlabel in the US in t (11;14) plasma cell disorders and is also included in the National Comprehensive Cancer Network (NCCN) guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A real-world experience of 18 RRMM patients with t(11;14) at diagnosis treated with venetoclax as a single agent (starting with a dose of 100 mg daily and increasing to a maximum dose of 400 mg daily) was recently reported (44). Six patients (33%) achieved a response ≥PR; the dominant nonhematological adverse event (AE) was nausea, while the hematological AEs were neutropenia and thrombocytopenia.…”
Section: Venetoclax Single Agentmentioning
confidence: 99%
“…An open-label, randomized, multicenter, three-arm phase 1b/ 2 study (NCT03312530) of cobimetinib (a MEK inhibitor) administered as a single agent and in combination with venetoclax +/-atezolizumab (an engineered MoAb of IgG1 isotype against protein programmed cell death-ligand 1) is currently under investigation in 49 RRMM patients who had received three to five prior therapies, including a PI and an IMiD (43). The patients are randomized 1:2:2 to cobimetinib (arm A), cobimetinib+venetoclax (arm B), or cobimetinib+venetoclax+ atezolizumab (arm C).…”
Section: Venetoclax In Combination With Other Drugsmentioning
confidence: 99%